What will be the value of dy/dx = (x + 2y + 3)/(2x + 3y + 4)?

(a) [(2 + √3)/2√3 * (log (√3(y + 2) – (x – 1))) + (2 – √3)/2√3 * (log (√3(y + 2) – (x – 1)))]

(b) [(2 + √3)/2√3 * (log (√3(y + 2) + (x – 1))) – (2 – √3)/2√3 * (log (√3(y + 2) + (x – 1)))]

(c) [(2 + √3)/2√3 * (log (√3(y + 2) – (x – 1))) – (2 – √3)/2√3 * (log (√3(y + 2) – (x – 1)))]

(d) [(2 + √3)/2√3 * (log (√3(y + 2) + (x – 1))) – (2 – √3)/2√3 * (log (√3(y + 2) – (x – 1)))]

This question was addressed to me in an interview for internship.

I would like to ask this question from Linear First Order Differential Equations topic in division Differential Equations of Mathematics – Class 12

NCERT Solutions for Subject Clas 12 Math Select the correct answer from above options

Interview Questions and Answers, Database Interview Questions and Answers for Freshers and Experience

Correct choice is (c) [(2 + √3)/2√3 * (log (√3(y + 2) – (x – 1))) – (2 – √3)/2√3 * (log (√3(y + 2) – (x – 1)))]

Best explanation: Put x = X + h, Y = Y + k,

We have, dY/dX = (X + 2Y +(h + 2k + 3))/ 2X + 3Y + (2h + 3k + 4)

So, (a – b)x = (a – b)

To determine h and k we set,

2h + 3k + 4 = 0 and h + 2k + 3 = 0

=> h = 1 and k = – 2

Therefore, dY/dX = (X + 2Y) / (2X + 3Y)

Putting Y = VX, we get,

V + X dV/dX = (1 + 2V)/(2 + 3V)

= (1 + 2V)/(3V^2 – 1)*dV = -dX/X

=> [(2 + √3)/(2(√3V – 1)) – (2 – √3)/(2(√3V – 1))] dV = -dX/X

Simplifying it further, we get;

[(2 + √3)/2√3 * (log (√3Y – X)) – (2 – √3)/2√3 * (log (√3Y – X))]

Where, X = x – 1 and Y = y + 2